PENDAMPINGAN MASYARAKAT DALAM PENGOLAHAN PRODUK PANGAN LOKAL SEBAGAI UPAYA PENINGKATAN EKONOMI KREATIF - Fibrianingtyas, A.; Rayesa, N.F.; Ali, D.A.; Ula, M. (Buletin Udayana Mengabdi, 2024)
Local economic development is a concept that focused to create jobs for local residents by utilizing local resources (natural, human, capital). Shallots are one of the most horticultural commodities that farmers have cultivated intensively for a long time. Shallot also become a source of income and employment opportunities that have a high contribution to the economy of the East Java region. The export value of shallots in 2018 was 1,678,637 USD. One of the areas in East Java that produces shallots is Nganjuk Regency. Especially in Rejoso District, shallot productivity ranks is the highest among other sub-districts in Nganjuk Regency. Apart from capital requirements, the monthly price of shallots in the last year has had relatively large fluctuations. The community also does not have the skills to process shallots into processed products, one of which is fried onions. Therefore, this community service aims to provide facilitate to the community, especially to women who join the family welfare education in processing shallots into fried onions. Keywords : Shallot, Facilitating, Community Services, Nganjuk Regency